2005
DOI: 10.1055/s-2005-837778
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on a Mixture of Fatty Acids from Sugar Cane (Saccharum officinarum) Wax Oil in Animal Models of Hypersensitivity

Abstract: A mixture of fatty acids obtained from sugar cane wax oil, the main components of which are palmitic, oleic, linoleic and linolenic acids, was evaluated topically in two experimental models of hypersensitivity: the ear swelling response to ovalbumin in sensitized mice (ED50 edema: 0.63 +/- 0.06 mg/ear, ED50 myeloperoxidase: 0.56 +/- 0.04 mg/ear, ED50 degranulated cells: 0.70 +/- 0,08 mg/ear) and oxazolone-induced contact hypersensitivity in mice (ED50 edema: 1.63 +/- 0.26 mg/ear, ED50 myeloperoxidase: 1.50 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The relative content (mg/100 g) of each compound is listed in Table 1 and Table 2. Recently, evidence has been provided about the potent use of a mixture of fatty acids, in which the main components were oleic, linoleic, palmitic, and linolenic acids, for the treatment of cutaneous inflammatory and allergic disorders [9]. Fatty acids regulate immune responses, and it has been proved that they influence the incidence of IgE-mediated allergic disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative content (mg/100 g) of each compound is listed in Table 1 and Table 2. Recently, evidence has been provided about the potent use of a mixture of fatty acids, in which the main components were oleic, linoleic, palmitic, and linolenic acids, for the treatment of cutaneous inflammatory and allergic disorders [9]. Fatty acids regulate immune responses, and it has been proved that they influence the incidence of IgE-mediated allergic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to those reported previously. A recent report has indicated that fatty acids can exert a beneficial effect on lung disease, including some types of asthma [8], and that a combination of fatty acids was a potential therapeutic material for cutaneous inflammatory disorders and allergies [9]. As HD can be used as an effective anti-inflammatory material, we hypothesized that HD could inhibit airway inflammation.…”
Section: Introductionmentioning
confidence: 99%